Passive and causative in Sanskrit - Lowe, J; Molina Munoz, A; Ruppel, A (Edizioni Ca’ Foscari – Venice University Press, 2024)
To what extent can fine-grained statistical analysis provide evidence regarding syntactic patterns in corpus languages like Sanskrit, particularly in cases where the interaction of multiple syntactic phenomena obscures the evidence? We investigate the value of a correlation matrix for bivariate data analysis in relation to varying syntactic patterns in a relatively poorly attested yet productive construction in Classical Sanskrit: the passive of the causative (‘passive causative’). The interaction of causative and passive is complex in Sanskrit, but we show that even in the case of low frequency data, syntactic conclusions can be drawn from such interactions when detailed statistical analysis is employed. In particular, our analysis speaks to the status of the ergative in Sanskrit.